Development of mouse preimplantation embryos in space. Issue 9 (11th April 2020) - Lei, Xiaohua; Cao, Yujing; Ma, Baohua; Zhang, Yunfang; Ning, Lina; Qian, Jingjing; Zhang, Liwen; Qu, Yongcun; Zhang, Tao; Li, Dehong; Chen, Qi; Shi, Junchao; et al.
Abstract: The development of life beyond planet Earth is a long-standing quest of the human race, but whether normal mammalian embryonic development can occur in space is still unclear. Here, we show unequivocally that preimplantation mouse embryos can develop in space, but the rate of blastocyst formation and blastocyst quality are compromised. Additionally, the cells in the embryo contain severe DNA damage, while the genome of the blastocysts developed in space is globally hypomethylated with a unique set of differentially methylated regions. The developmental defects, DNA damage and epigenetic abnormalities can be largely mimicked by the treatment with ground-based low-dose radiation. However, the exposure to simulated microgravity alone does not cause major disruptions of embryonic development, indicating that radiation is the main cause for the developmental defects. This work advances the understanding of embryonic development in space and reveals long-term extreme low-dose radiation as a hazardous factor for mammalian reproduction.